(untitled) (International Seven Journal of Multidisciplinary, 2024)
The present research work had as a research problem, how to simulate the dynamics of the dengue model in the province of Condorcanqui, department of Amazonas, and consisted of finding a system of differential equations containing unknowns and parameters (the latter had to be found numerically), the general objective of our research was to simulate the dynamics of the dengue model in the province of Condorcanqui, department of Amazonas. As for the methodology, we used the hypothetical-deductive methods, directed observation and the quantitative method, which are typical of the sciences. It was concluded that the SIR model simulates the dynamics of the dengue model in the province of Condorcanqui, department of Amazonas.